1972
DOI: 10.1002/aja.1001350106
|View full text |Cite
|
Sign up to set email alerts
|

A study on division of primordial germ cells in the early chick embryo

Abstract: The purpose was to determine the sites, times and frequency of mitotic activity in primordial germ cells in the white Leghorn chick embryo during the period of migration. Colchicine was employed to facilitate the identification of dividing germ cells in embryos ranging in age from 18 hours to five days of incubation (stages 3-27). An increase in the number of germ cells was observed during the period of migration, due primarily to proliferation of intraembryonic cells, since no significant increase in the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 22 publications
3
16
1
Order By: Relevance
“…It is not yet clear what actually controls asymmetric germ cell distribution. It is possible that chemotactic and/or mitogenic factors play a role in germ cells migration, and it has been proposed that the left gonadal ridge secretes such factors more than the right, leading to increased PGCs migration and/or division in the left gonad (Witschi, 1935;Swartz and Domm, 1972). One study supported this by showing that engrafted quail PGCs differentially colonized the left and right presumptive gonads at limb bud stages (HH 18-24) (Didier and Fargeix, 1976).…”
Section: Asymmetric Germ Cell Distribution In Female and Male Embryonsupporting
confidence: 53%
“…It is not yet clear what actually controls asymmetric germ cell distribution. It is possible that chemotactic and/or mitogenic factors play a role in germ cells migration, and it has been proposed that the left gonadal ridge secretes such factors more than the right, leading to increased PGCs migration and/or division in the left gonad (Witschi, 1935;Swartz and Domm, 1972). One study supported this by showing that engrafted quail PGCs differentially colonized the left and right presumptive gonads at limb bud stages (HH 18-24) (Didier and Fargeix, 1976).…”
Section: Asymmetric Germ Cell Distribution In Female and Male Embryonsupporting
confidence: 53%
“…Ectopic PGCs may gradually and slightly increase in number by their own cell division. In regard to this, Swartz and Domm (1972) observed dividing PGCs in extragonadal sites in the chick, and also reported that in the figure). G, future gonadal area.…”
Section: Discussionmentioning
confidence: 70%
“…After leaving the blood vessels, the PGCs finally migrate into the developing gonadal anlagen in the embryo proper (Swift, 1914;Fujimoto et al, 1976). However, it has been reported that, in the chick embryo, some PGCs deviate from the normal route of their migration and are found in extragonadal sites (Swartz and Domm, 1972). In lower vertebrates, a similar abnormal localization of PGCs has been noted; 25% of the germ cells are ectopic in elasmobranchs (Beard, 1902) and 5% in urodeles (Humphrey, 1925).…”
mentioning
confidence: 98%
“…We found that the number of quail PGCs was reduced significantly by two doses of genistein. It has been reported that mitotic figures can be found in dividing PGCs during germ cell migration (Swartz and Domm 1972). Thus, genistein may inhibit germ cell division and proliferation.…”
Section: Discussionmentioning
confidence: 99%